Unveiling the Differential Impact of Diabetes on Maxillofacial Space Infection Spread and Progression: A Comparative Analysis - Vijayvargiya, Dhiral; Sharma, Amit Kumar; Sharma, Sunil; Agarwal, Prateek; Pandey, Abhishek; Pradhan, Vaishali (Journal of Neonatal Surgery, 2025)
Introduction: This study compared head and neck infection characteristics between diabetic and non-diabetic patients. We investigated the spread of infection, causative pathogens, glycemic control, and comorbidities. Methods: A study was conducted on 48 patients with maxillofacial infections, comparing those with and without diabetes. Febrile status, blood work, pathogen identification, and antibiotic sensitivities were analysed. Results: Diabetics exhibited significantly greater spread of infection. Streptococcus, Staphylococcus, and Klebsiella were prevalent in both groups. Comorbidity rates were similar. Diabetics had higher HbA1c and random blood sugar. Conclusion: Diabetes significantly increases the spread of head and neck infections. Prompt treatment and optimization of glycaemic control are crucial for these patients. Further research should explore comorbidity influences.